Wheat head silage and corn silage for growing steers - Bolsen, K.K.; Conway, K.L.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Two trials were conducted to evaluate two varieties of wheat head silage (Parker and Blue Boy) and whole-plant corn silage in growing rations for steers. Each silage was fed to 21 steers for 122 days. All steers were full-fed a 12.5% crude protein ration containing 86% silage and 14% supplement. Steers fed corn silage gained faster, consumed more dry matter and were more efficient than steers fed either wheat head silage ration. Gain and feed consumption were greater for steers fed Blue Boy than for those fed Parker. Ration dry matter digestibility was higher for the corn silage ration than for either wheat head silage ration.
Keywords: Beef; Wheat silage; Corn silage; Steers